PENGARUH KOMPETENSI, INDEPENDENSI, TEKANAN ANGGARAN WAKTU DAN PROFESIONALISME TERHADAP KUALITAS AUDIT (Studi Empiris Pada Auditor Kantor Akuntan Publik di Kota Semarang) - Pinkky Sisvianingrum, 13.05.52.0049; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of competence, independence, time budget pressure, and professionalism on audit quality in KAP Semarang and also to find empirical evidence to examine the influence of competence influence, independence, time budget pressure, and professionalism on quality in KAP Semarang. This research is done in KAP Semarang by Accidental Sampling method that is sample determination technique by chance, that is anyone who accidentally or Accidental met withÂ researcher, can be used as sample, if seen by person who happened to meet it suitable as source of data. This research yield 40 sample that can be processed, from 60 distributed questionnaires. Source of data derived from respondents answers by using questionnaires that are distributed directly in KAP Semarang. Method of analysis used is multiple linear regression method. The results of this study indicate that there is an influence of independence on audit quality in KAP Semarang. While the competence, time budget pressure, and professionalism have no effect on audit quality.Keywords: Competence, Independence, Time Budget Pressure, and Professionalism